Dr. Analyzing Trafficking in Person in Religious and Cultural Context: Pakistan Perspective: Pakistan Perspective - Razi, Naseem Razi; Abbas, Ghulam Abbas; Zahoor, Rashida Zahoor (Journal of Peace, Development and Communication, 2021)
The modern world has declared trafficking in person as modern-day slavery while Pakistan is considered as a major contributor in the rise of human trafficking in South Asia. In this context, this research aims to test the issue in the light of the Qur’an, Sunnah (pbuh) and sociocultural context of Pakistan. This study argues that Islam is the only religion which showed its greatest concerns towards the issues of trafficked persons. It also aims to recognize the efforts of the modern world to overcome the issue. This study, however, concludes that despite much legislation nationally and internationally, the issue could not be resolved and is going to worsen every day. All this thus, demands an overhauling of the prevailing socio-cultural and legal context. It recommends Renaissance of the ethics of Islam and the policies of the Holy Prophet (pbuh) and Hadrat Umar to overcome the evils of trafficking in person in Pakistan.